Antimicrobial Properties of Highly Elastic Conductive Poly(ethylene terephthalate)/Multiwalled Carbon Nanotube Fabrics. (13th August 2022) - Varan, Nilüfer Y; Altay, Pelin; Çaydamlı, Yavuz
This research focused on understanding the microbe killing mechanism of the antimicrobial properties of highly elastic conductive poly(ethylene terephthalate) (PET)/multi-walled carbon nanotube (MWCNT) powernet fabrics with the help of electric fields and highly elastic structure. In this study, PET/MWCNT fabrics containing three different percentages of MWCNT were knitted and characterized with antimicrobial activity, cytotoxicity, electromagnetic shielding properties, DSC analyses, stiffness tests, and pressure measurements using wireless pressure sensors. Results show that MWCNT has a statistically significant effect on antibacterial activity, cytotoxicity, electromagnetic shielding, stiffness, and exerted pressures. PET/MWCNT fabrics showed excellent antibacterial activity against tested germs; S. aureus and E. coli . A statistically significant increase in percentage reduction of bacteria was observed with the increase in carbon nanotube nanoparticle concentration, accompanied by a good laudering durability even after 20 washing cycle. In terms of cytotoxicity tests, all PET/MWCNT samples were found to have over 70% average relative cell viability, indicating that they are noncytotoxic without interrupting the cell line and primary cell growth in vitro. The materials have provided longer conductive networks and formed electromagnetic shielding at the range of 22.79 dB-25.77 dB at the frequency of 0–1.30 GHz. Moreover, MWCNT concentration did not lead to considerable changes in physical properties like stiffness and exerted pressure properties. Characterization analyses confirmed the changes in the chemical structure of the PET/MWCNT.